Ameliorative potential of thymoquinone in nicotine-treated rats: Sperm characteristics and expression level of PRM1 and TNP2 genes / Farah Dayana Rosli - Farah Dayana , Rosli (2019)
Thymoquinone (TQ), the main constituent of the volatile oil derived from Nigella sativa has been extensively studied for its various therapeutic properties. This study was conducted to assess the effects of TQ in ameliorating the injurious state of sperm in infertility-induced rats caused by nicotine, the active component in cigarettes. Experiments were conducted on adult male Sprague Dawley rats which were divided into four groups: 1) control group, received normal saline orally for 60 days; 2) nicotine group, was subcutaneously injected with 5 mg/kg/day nicotine for 30 days and then given normal saline for next 30 days; 3) TQ group, was given normal saline for 30 days and followed by TQ 5 mg/kg/day for another 30 days; 4) nicotine-TQ group, received 5 mg/kg/day nicotine for 30 days and followed by TQ 5mg/kg/day for 30 days. The sperm count, motility, membrane integrity, mitochondrial function and DNA integrity in sperm were evaluated. Also, the expression level of genes responsible for chromatin condensation, PRM1 and TNP2 were analyzed. Results showed significantly lower number of sperm count (26.72 ± 1.64 106/ml) and sperm motility (66.24 ± 1.01 %) in nicotine group but higher number in nicotine-TQ group (30.97 ± 0.88 106/ml and 85.02 ± 2.24 %, respectively; p<0.05). Results of sperm membrane integrity test and the number of MitoTracker positive sperm also showed a significantly lower percentage in nicotine group (47.34 ± 0.69 % and 75.68 ± 0.90 %, respectively) but a notable improvement in nicotine-TQ group was observed (52.58 ± 1.14 % and 79.08 ± 0.74 %, respectively). Moreover, TQ significantly decreased DNA fragmentation in sperm of nicotine treated rats in Comet assay (2.40 %; p<0.05). Sperm mitochondrial function showed a significant correlation with DNA damage which was inversely proportional to each other (r = -0.480; p<0.01). By RT-qPCR analysis, the expression level of PRM1 and TNP2 genes were evaluated to ascertain if DNA damage occurring in this study as a result of dysregulation of chromatin protein gene. There were no changes in expression level of PRM1 in nicotine, TQ and nicotine-TQ group, whilst TNP2 was downregulated in nicotine group (0.047 ± 0.009) and slightly but significantly upregulated in nicotine-TQ group (0.111; p<0.05). This suggests that the DNA damage observed in this study may not be induced by abnormal chromatin packaging. Nevertheless, further investigations on the effects of nicotine and TQ on TNP2 need to be explored in the future. In conclusion, the present study demonstrates the potential benefits of TQ in improving the sperm quality of nicotine-induced damage.